Analisis Kontribusi Retribusi Pasar Terhadap Pendapatan Asli Daerah Kabupaten Gorontalo - Pulukadang, Putri Ayimi; Olilingo, Fahrudin Zain; Abdul, Irawati (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to analyze the contribution and effectiveness of market levies to Local Own-Source Revenue (PAD) in Gorontalo Regency. Market levies are one component of PAD that has great potential, but their realization is often below the set target. This study uses a descriptive quantitative approach with secondary data in the form of market levy and PAD revenue reports for Gorontalo Regency from 2019 to 2024. The analysis technique used is contribution and effectiveness analysis. The results show that the contribution of market levies to PAD in Gorontalo Regency is very low, with an average contribution of less than 1% per year. However, the effectiveness of market levy collection shows varying results. In some years, the effectiveness is relatively high, even exceeding 100%, while in other years it is still below the target. Factors that influence these achievements include the level of trader compliance, the efficiency of the collection system, the quality of market facilities, and supervision from the local government. The conclusion of this study is that market levies have not made a significant contribution to the Gorontalo Regency's PAD. Therefore, strategic efforts are needed to optimize management and collection in order to increase regional revenue in a sustainable manner.